RNase H1-Dependent Antisense Oligonucleotides Are Robustly Active in Directing RNA Cleavage in Both the Cytoplasm and the Nucleus - Liang, Xue-Hai (Mol Ther, 2017)
RNase H1-dependent antisense oligonucleotides (ASOs) are active in reducing levels of both cytoplasmic mRNAs and nuclear retained RNAs. Although ASO activity in the nucleus has been well demonstrated, the cytoplasmic activity of ASOs is less clear. Using kinetic and subcellular fractionation studies, we evaluated ASO activity in the cytoplasm. Upon transfection, ASOs targeting exonic regions rapidly reduced cytoplasmically enriched mRNAs, whereas an intron-targeting ASO that only degrades the nuclear pre-mRNA reduced mRNA levels at a slower rate, similar to normal mRNA decay. Importantly, some exon-targeting ASOs can rapidly and vigorously reduce mRNA levels without decreasing pre-mRNA levels, suggesting that pre-existing cytoplasmic mRNAs can be cleaved by RNase H1-ASO treatment. In addition, we expressed a cytoplasm-localized mutant 7SL RNA that contains a partial U16 small nucleolar RNA (snoRNA) sequence. Treatment with an ASO simultaneously reduced both the nuclear U16 snoRNA and the cytoplasmic 7SL mutant RNA as early as 30 min after transfection in an RNase H1-dependent manner. Both the 5′ and 3′ cleavage products of the 7SL mutant RNA were accumulated in the cytoplasm. Together, these results demonstrate that RNase H1-dependent ASOs are robustly active in both the cytoplasm and nucleus.